(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To perform the analysis of the results of primary open-angle glaucoma (POAG) patients’ examination at presentation and to build objective criteria for the development and progression of the disease. Materials and Methods: One hundred and seventy two patients (344 eyes) diagnosed with POAG were involved into the study. In addition, the control group comprised 98 volunteers (196 eyes) diagnosed with no POAG. The age at presentation ranged from 40 to 74 years with a mean of 57.3±1.1 years. Statistical analyses were performed using MedStat and MedCalc v.15.1 (MedCalc Software bvba). Results: Disease duration was found to increase from 0 to 3 years with an increase in the stage of POAG (Н=10869; p=0.00Е-01). Both absolute IOP values and IOP categories progressively increased with an increase in the stage of POAG (Н=88.76, р=0.00Е-01 and Н=90.13, р=0.00Е-01, respectively). Two indices, SDPOAG (speed of POAG development, expressed as stage/life year), and SPPOAG (speed of POAG progression, expressed as stage/disease year), were proposed as measures for assessing speed of the pathological process. These were found to progressively increase with an increase in the stage of the pathological process (р<0.05). The effect of SPPOAG on the stage of POAG was found to be statistically significant (F=21.1; p=2.16E-11).